(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research delves into the profound impact of colonial rule on Garo Hills’ socio-economic frameworks, employing a comparative analysis spanning historical and contemporary perspectives. Employing an interdisciplinary methodology, the study explores the intricate dynamics that shaped the region during colonial rule, unraveling enduring impacts on socio-economic structures. Comprehensive examination includes pre-colonial institutions, consequences of colonial policies, resistance movements, and the present socio-economic environment, offering a nuanced understanding of Garo Hills’ developmental trajectory and the persistent legacies of colonial governance.